Spatial distribution of scorpions according to the socioeconomic conditions in Campina Grande,State of Paraíba, Brazil - Thassiany Sarmento Oliveira de Almeida; Sayonara Maria Lia Fook; Francisco Oscar de Siqueira França; Tânia Maria Ribeiro Monteiro; Edwirde Luiz Silva; Lidiane Cristina Félix Gomes; Aline Maiara Galdino Farias (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract: INTRODUCTION: Due to its frequency and morbidity, such as that caused by scorpions have achieved public health importance in certain regions of the world. The present exploratory ecological study aimed to characterize the epidemiological profile and spatial distribution of scorpion stings in Campina Grande, State of Paraíba in Northeastern Brazil. METHODS: Geographical information system techniques were used to record the scorpion stings, and Google Earth software, Track Maker, and ArcGIS 10 Esri were used as geocoding databases. The Moran test was used to evaluate spatial correlation, and the Pearson chi-square test was used to analyze associations between scorpion stings and socioeconomic variables. RESULTS: The study evaluated 1,466 scorpion stings. Envenomations were more frequent among women (n = 908, 61.9%), and most patients were aged 13-28 years (n = 428, 29.2%). The Southern region of the city had the largest number of registered cases (n = 548, 37.4%), followed by the Western region (n = 510, 34.8%). CONCLUSIONS: Spatial analysis of scorpionism revealed an irregular occurrence in Campina Grande. Further, no association was observed between the socioeconomic factors analyzed and the geographic location of the scorpion envenomations. Detection of spatial areas with an increased risk of scorpionism can help prioritize adoption of preventive measures in these regions to reduce the associated incidence and morbidity.